The null hypothesis is always rejected with statistical tricks: Why do you need it? - Paniagua, Freddy A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
Ferguson (2015) observed that the proportion of studies supporting the experimental hypothesis and rejecting the null hypothesis is very high. This paper argues that the reason for this scenario is that researchers in the behavioral sciences have learned that the null hypothesis can always be rejected if one knows the statistical tricks to reject it (e.g., the probability of rejecting the null hypothesis increases with p = 0.05 compare to p = 0.01). Examples of the advancement of science without the need to formulate the null hypothesis are also discussed, as well as alternatives to null hypothesis significance testing-NHST (e.g., effect sizes), and the importance to distinguish the statistical significance from the practical significance of results.